Recommendations for the adjuvant use of the poly-antibiotic–resistant probiotic Bacillus clausii (O/C, SIN, N/R, T) in acute, chronic, and antibiotic-associated diarrhea in children: consensus from Asian experts - De Castro, JA (Springer Science and Business Media LLC, 2021)
10.1186/s40794-020-00120-4